2005
DOI: 10.1681/asn.2004100852
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Angiotensin II Receptor Blockade Reduces (Intra)Renal Vascular Resistance in Patients with Type 2 Diabetes

Abstract: Increased (intra)renal activity of the renin-angiotensin system may cause a persistent increase in renovascular resistance and intraglomerular pressure in patients with diabetes, thus contributing to the development of diabetic renal damage. The effect of chronic angiotensin II subtype 1 receptor blockade on (intra)renal hemodynamics in patients with type 2 diabetes was examined in a double-blind parallel group study. Patients were treated with 40 mg of olmesartan (n ‫؍‬ 19) or placebo (n ‫؍‬ 16), and renal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 39 publications
1
51
0
3
Order By: Relevance
“…Moreover, modulation of DDAH activity to lower plasma ADMA levels may represent a novel therapeutic target to retard progression. In this respect, inhibition of the renin-angiotensin system may not be enough, because we could not find a significant effect of chronic angiotensin II receptor blockade on plasma ADMA concentrations in a recent double-blind, placebo-controlled, randomized study (33). Thus, other treatment strategies to reduce ADMA in patients with kidney diseases should be evaluated.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, modulation of DDAH activity to lower plasma ADMA levels may represent a novel therapeutic target to retard progression. In this respect, inhibition of the renin-angiotensin system may not be enough, because we could not find a significant effect of chronic angiotensin II receptor blockade on plasma ADMA concentrations in a recent double-blind, placebo-controlled, randomized study (33). Thus, other treatment strategies to reduce ADMA in patients with kidney diseases should be evaluated.…”
Section: Discussionmentioning
confidence: 88%
“…[37][38][39] ARBs, particularly telmisartan and olmesartan, also exert antidiabetic effects through their regulation of insulin sensitivity and reduce not only urinary albumin excretion but also urinary 8-OHdG and L-FABP excretion. 40 Statins have been shown to ameliorate tubular and podocyte injury, preserve GFR and reduce proteinuria in renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological agents that have been tested for their ability to modify ADMA levels in humans include drugs that interfere with the renin-angiotensin system (RAS) by either blocking the formation [angiotensin-converting enzyme (ACE) inhibitors] or pharmacological action [angiotensin receptor blockers (ARBs)] of angiotensin II (ANG II). Although some investigators found significant reductions of ADMA levels in patients treated with RAS-blocking agents (2,4,9,15,16,27,42), other studies have failed to confirm these findings (10,40). Sound interpretation of the aforementioned clinical trials is complicated due to differences in study design, study cohorts, treatment regimen, and the use of different bioanalytical methods to determine ADMA levels.…”
mentioning
confidence: 99%